1997
DOI: 10.1007/s002239900370
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Structure and Density in Determining Vertebral Bone Strength

Abstract: The strength of bone is determined not only by bone density but also by structure. Therefore, quantification of the structure in radiographs by texture parameters may result in a better prediction of fracture risk. Since in radiographs density and structure are strongly correlated, the predictive power of texture parameters should be corrected for the influence of BMD to determine the additional information conveyed by these parameters. In this study, we evaluated the predictive power of various texture parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…3) Recent research suggests that bone mineral density (BMD) is not a sufficient predictor of whole bone mechanical properties, while BMD is related to bone strength and fracture risk. 4,5) In untreated patients with the same BMD, fracture risk varies with age and perhaps with gender and race. 6) Therefore, the influences of still unidentified parameters controlling bone mechanical properties should be determined.…”
Section: Introductionmentioning
confidence: 99%
“…3) Recent research suggests that bone mineral density (BMD) is not a sufficient predictor of whole bone mechanical properties, while BMD is related to bone strength and fracture risk. 4,5) In untreated patients with the same BMD, fracture risk varies with age and perhaps with gender and race. 6) Therefore, the influences of still unidentified parameters controlling bone mechanical properties should be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases multiple regression models are tested to check whether inclusion of texture parameters increases determination coefficient of parameters directly related to fracture risk e.g., fracture strength or apparent Young's modulus as compared to bone density only. The published results are not however encouraging -the texture analysis improves the prediction of mechanical parameters by at most a few percent (Veenland et al, 1997;Cortet et al, 1999).…”
Section: Gray-level Methods For Characterizing Trabecular Bone Structurementioning
confidence: 92%
“…In particular, the gray-level images of trabecular bone have been analyzed, using the methods developed for texture characterization. One of the possible approaches is based on the co-occurrence of matrix and its derived parameters (Haralick et al, 1973;Veenland et al, 1997). Firstly, histogram equalization is performed: the number of gray levels is reduced to some number N and gray-level intensities are redistributed in such way that the probability of occurrence for all gray-levels is equalized.…”
Section: Gray-level Methods For Characterizing Trabecular Bone Structurementioning
confidence: 99%
“…Materka et al (2000) bone mineral density estimated by means of Dualphoton Absorptiometry (DXA) based on cooccurrence matrix texture analysis by computing the standard DXA technique and the image mean, standard deviation, skewness, kurtosis, energy, entropy, fractal dimension in vertical dimension and variance-based fractal dimension and examine their correlations. Veenland et al (1997) suggested that the power of texture parameters is corrected for the influence of BMD to determine the additional information indicated by these parameters since in radiographs density and structure are strongly correlated. The predictive power of these texture parameters are obtained through the Grey-Level Dependence Method and the Morphological Gradient Method by examining Correlation coefficients of the investigated texture parameters…”
Section: Introductionmentioning
confidence: 99%